PENGARUH STRES KERJA DAN KOMITMEN ORGANISASI TERHADAP SEMANGAT KERJA KARYAWAN PT. BPR INDOMITRA MEGA KAPITAL PEKANBARU - Fatimah, Siti; ', Marzolina; ', Sjahruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect simultaneously and partially Job Stress and Organizational Commitment Against Employee Dicipline At PT. BPR Indomitra Mega Kapital Pekanbaru. Consists of three variables: the dependentvariable and two independent variables. The study was conducted with a sample of 72 people. Research using census techniques by giving questionnaires to the respondents. In terms of data analysis, using qualitative and quantitative methods using SPSS (Statistical Package for Social Sciences) version 20.0. The analysis showed that the variables Job Stress and Organizational Commitment affect the Employee Dicipline At PT. BPR Indomitra Mega Kapital Pekanbaru. Job Stress and Organizational Commitment jointly affect the Employee Dicipline At PT. BPR Indomitra Mega Kapital Pekanbaru significant 0.000. The influence of partial variable Job Stress and Organizational Commitment to Employee Morale At PT. BPR Indomitra Mega Kapital Pekanbaru. The work stress variables negativelyaffect the Employee Dicipline At PT. BPR Indomitra Mega Kapital Pekanbaru while variable Organizational Commitment positive effect on Employee Morale At PT. BPR Indomitra Mega Kapital Pekanbaru.Keywords: Job Stress, Organizational Commitment, and Employee Dicipline.